PENGGUNAAN LUMPUR AKTIF UNTUK MENURUNKAN KADAR Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), dan LOGAM BERAT JENIS TIMBAL (Pb) dan CADM IUM (Cd) PADA LIMBAH CAIR PENCELUPAN INDUSTRI BATIK - RAFICHA RACHMA; I W REDI ARYANTA; I.W. Kasa (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2012)
In the production process, batik dyeing industry use a lot of water and chemicals in the coloring or dyeing fabric dyeing wastewater batik. Batik dyeing waste industry typically have concentrations of chemical oxygen demand (COD) and biological oxygen demand (BOD) and heavy metals that exceed quality standards set by the government. In an effort to overcome the problems posed by wastewater, the wastewater treatment process must be done before the waste is discharged into aquatic environment. One of the biological wastewater treatment system that is able to reduce levels of contamination are industrial wastewater is activated sludge system. This research was conducted to determine the optimal time and time effectiveness of treatment with activated sludge to reduce levels of COD, BOD, and Pb in the batik industry wastewater. In this research using activated sludge by taking a fixed volume on sampling from hour o to hour 24 so as to produce organic compounds that remain much lower concentrations can result in COD, BOD, and Pb. This is because the longer the settling time of the volume of waste activated sludge with variable sampling and at the same time a decrease in the percentage levels of COD, BOD, and Pb greater. The results of this research found that activated sludge best influence in lowering the levels of COD, BOD, and Pb. This is due to the activity of microorganisms that have given nutrient and insufficient oxygen in aeration process with the longest time that the ability of the microbes in the sludge to oxidize organic materials with the highest effectiveness in the waste. After going through treatment with activated sludge showed that the optimal time of activated sludge treatment to decrease the levels of COD in wastewater dyeing batik industry is 12 hours, the reduced levels of BOD is 12 hours, and to decrease levels of Pb is 8 hours.